The Juridical Study on the Implementation of the Ijarah Muntahiya bi at-Tamlik Contract in the Concept of Luzumu al-‘Aqdi - Bawono, Bambang Tri; Laksana, Andri Winjaya (ADDIN, 2022)
The purpose of this study was to examine and analyze the implementation of the Ijarah Muntahiya bi at-Tamlik contract in the conception of Luzumu al-‘Aqdi. The approach method used in this research was sociological juridical. The results of this study indicated that the implementation of the Ijarah Muntahiya bi at-Tamlik contract at Bank Syariah Indonesia (Indonesian Sharia Bank, BSI) Semarang Branch Office in the concept of Luzumu al-‘Aqdi actually shows the occurrence of legal uncertainty. This is because the implementation of the Ijarah Muntahiya bi at-Tamlik contract should only be carried out through buying and selling, not grants. The implementation of the Ijarah Muntahiya bi at-Tamlik contract can only use a sale and purchase contract because this contract is part of the ijarah contract which aims to obtain profit or profit, while the grant contract is one of the tabarru’ contracts which aims to help each other and seek the pleasure of Allah alone. Besides that, implementation of the Ijarah Muntahiya bi at-Tamlik contract settlement through the sale of the Ijarah Muntahiya bi at-Tamlik object results in legal uncertainty, so that this has the potential to harm the musta’jir or the debtor in the event of bad credit or default. This is because the musta’jir or debtor should not be said to have debt, considering that the contract that is built is ijarah first which will end with ownership through buying and selling or grants, not buying and selling which is required by ijarah because its implementation is carried out in installments.